Hormesis: a conversation with a critic. - Calabrese EJ (Environmental Health Perspectives, 2009)
OBJECTIVE: In this commentary I respond to points raised in the commentary by Mushak [Ad hoc and fast forward: the science and control of hormesis growth and development. Environ Health Perspect 117:1333-1338 (2009)], which principally concerns studies by me and my colleagues concerning the frequency of hormesis in toxicology. DISCUSSION: In this commentary I demonstrate that Mushak's analysis contains critical statistical errors and misunderstandings of statistical concepts that invalidate its conclusions concerning the frequency of hormesis in the toxicologic literature. CONCLUSIONS: In his commentary Mushak offers no significant new conceptual insights, and his key technical criticisms of hormesis frequency findings are unfounded.